2004
DOI: 10.1161/01.str.0000131858.63829.6e
|View full text |Cite
|
Sign up to set email alerts
|

Remote Evaluation of Acute Ischemic Stroke in Rural Community Hospitals in Georgia

Abstract: Background and Purpose-Despite Food and Drug Administration approval of tissue-type plasminogen activator (tPA) for stroke, obstacles in the US health care system prevent widespread use. The Remote Evaluation for Acute Ischemic Stroke (REACH) program was developed to address these obstacles in rural settings. We have previously shown the reliability of the REACH system in performing a valid National Institutes of Health Stroke Scale (NIHSS) evaluation at the Medical College of Georgia (MCG). We now report on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 11 publications
4
75
1
2
Order By: Relevance
“…Many studies have demonstrated the utility of telestroke for assessing stroke severity [9][10][11][12] and for increasing the use of tPA among eligible patients. [13][14][15][16][17] Our findings add to this body of literature supporting the value of telestroke for improving tPA administration rates among patients with ischemic stroke presenting to community hospitals. We found that telestroke can be implemented safely and effectively in community hospitals, and that the beneficial effects (increased tPA utilization) occurred quickly after implementation without a significant lag period and without any corresponding change in complications.…”
Section: Discussionsupporting
confidence: 57%
“…Many studies have demonstrated the utility of telestroke for assessing stroke severity [9][10][11][12] and for increasing the use of tPA among eligible patients. [13][14][15][16][17] Our findings add to this body of literature supporting the value of telestroke for improving tPA administration rates among patients with ischemic stroke presenting to community hospitals. We found that telestroke can be implemented safely and effectively in community hospitals, and that the beneficial effects (increased tPA utilization) occurred quickly after implementation without a significant lag period and without any corresponding change in complications.…”
Section: Discussionsupporting
confidence: 57%
“…The authors conducted both a bedside and a remote evaluation for 20 patients who presented in rural community hospitals and found that the correlation between the 2 modalities was very strong. 42 In 2005, MCG researchers published data on 194 acute stroke patient consultations provided between March 2003 and May 2005, which included 30 patients treated with tPA. 43 The authors concluded that their system "permits the rapid and safe use of tPA in rural community hospitals" (p 2018) and that time and experience help reduce onset to treatment time.…”
Section: Discussionmentioning
confidence: 99%
“…The consultant evaluates the data and makes a recommendation regarding thrombolytic therapy, and this recommendation is communicated to the mobile cart in the spoke hospital and can be added to the medical record. 42 In designing the system, the MCG team and the initial rural community hospital partners focused on ease of use. MCG made site visits to the early partner spoke hospitals and consulted extensively with the rural hospital emergency department staff in the design of the program.…”
Section: Operationsmentioning
confidence: 99%
“…The feasibility of performing the NIHSS-telestroke during actual thrombolytic consultations has been demonstrated in multiple observational cases series. The originating sites (ie, clinical setting where the patient is physically located) include (1) a remote Maryland facility using ISDN connections and a restructured NIHSS-telestroke (23 telemedicine cases), 38 (2) an isolated Massachusetts island hospital (24 telemedicine cases), 39 (3) 12 German community hospitals within an ISDN network (1123 cases), 40 (4) 2 Texas community hospitals using a fiberoptic network (328 cases), 41 (5) 8 rural Georgia hospitals using a cell phone or regular telephone service for audio and a 1-way videoconferencing system (75 patients 42 and 194 patients 43 ), and (6) 4 California community hospitals using HQ-VTC. 44 Assessing NIHSS reliability during remote acute telestroke consultations is problematic because acute telestroke consults are generally performed when local neurological evaluations are unavailable.…”
Section: Acute Stroke Setting Including Thrombolytic Evaluationmentioning
confidence: 99%